Thematic workshop: the Chemistry in electronic devices (Research, Society and Development, 2020)
The present work describes an action developed by the Institutional Program for Teaching Initiation Scholarships, of the Chemistry Degree course at the Federal University of Santa Maria in a public school, where a thematic workshop entitled “The Chemistry present in the Electronic Devices” was held. It consists of an exploratory qualitative research that aimed to work with different didactic resources, aiming to provide students with contextualized and interdisciplinary learning of chemical concepts. This argument is based on the defense of the need to introduce, in the classroom, pedagogical instruments and methodologies that allow the qualification of the use of chemical language by students. For that, we used some didactic resources for the development of the workshop, among them are: demonstrative lecture with the aid of experimentation, reading and discussion of Scientific Dissemination Materials, the application of a didactic game and the creation of posters aimed at raising awareness of students regarding the correct disposal of electronic waste.